Data‐Driven SuStaIn Model of Disability Progression in Amyotrophic Lateral Sclerosis - Giammarco Milella; Veria Vacchiano; Vittorio Velucci; Stefano Zoccolella; Rocco Liguori; Giovanni Defazio (Annals of Clinical and Translational Neurology, 2026)
ABSTRACT Objective To determine whether ordinal Subtype and Stage Inference (SuStaIn) applied to routine ALSFRS‐R item scores can identify reproducible disability progression patterns in amyotrophic lateral sclerosis (ALS) and provide clinically meaningful staging. Methods We analysed baseline ALSFRS‐R item responses from 866 PRO‐ACT participants. Ordinal SuStaIn inferred subtype‐specific sequences of functional deterioration and assigned each participant to a subtype and a SuStaIn‐derived functional stage. Longitudinal stability was assessed across 3625 consecutive follow‐up visit pairs from 697 participants. Structural reproducibility was evaluated in an independent cohort of 301 consecutive ALS patients. Associations of baseline subtype and stage with survival and subsequent ALSFRS‐R decline were examined using Cox and piecewise‐linear models. Results A three‐subtype solution identified fine motor‐, gross motor‐ and bulbar‐predominant patterns of early disability. Within each subtype, SuStaIn reconstructed ordered multidomain sequences of functional deterioration and assigned each participant a SuStaIn‐derived stage. Subtype assignment was stable across 90.4% of consecutive visit pairs, and stage was non‐decreasing in 98.8%. Subtype‐specific event ordering was reproduced in the validation cohort. Higher baseline stage was associated with increased mortality risk in the fine motor‐ and gross motor‐predominant subtypes, but not clearly in the bulbar‐predominant subtype. Baseline stage showed subtype‐dependent, non‐linear associations with subsequent functional decline, with acceleration up to mid‐stage breakpoints in the fine motor‐ and gross motor‐predominant subtypes and less evident stage‐dependent acceleration in the bulbar‐predominant subtype. Interpretation Routine ALSFRS‐R item‐level data can define clinically interpretable ALS progression subtypes and latent SuStaIn‐derived functional stages. Joint subtype‐stage modelling may refine prognostic stratification and support prognosis‐informed trial enrichment.